Inguinal hernia relapse. Pathogenetic and therapeutic factors - Croci, Fabio; Gastambide, Carmelo; Terra, Eneas; Cordal, Adriana (Cirugía del Uruguay, 1983)
Inguinal hernia relapse from the pathogenetic and therapeutic point of view is studied, in a serie of 248 cases with a follow up of at least 3 years. The importance of technical errors ín the pathogeny in pointed out. The utility of different repair procedures in considered. The Cooper's ligament importance and the utility of prostetic mesh are pointed out.